2005
DOI: 10.1111/j.1365-2850.2004.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of care in psychiatric post‐ward outpatient services – conceptions of patients and personnel concerning factors contributing to the continuity of care

Abstract: A structural change of the psychiatric services was started in Finland in the 1980s. Its primary objective was to shift the main emphasis from hospital to outpatient services. Hence, the number of psychiatric beds has declined to a third of the maximum rate, inpatient periods have shortened and the number of outpatient appointments has increased significantly. International research shows that when the emphasis of psychiatric services shifts to outpatient services and hospitalization becomes short-term, divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…1997). On the other hand, fellow patients can, as in our study, be supportive and understanding (Lindström 1995, Wood & Pistrang 2004) and the relationship may remain important, even after discharge (Hautala‐Jylha et al . 2005).…”
Section: Discussionmentioning
confidence: 71%
“…1997). On the other hand, fellow patients can, as in our study, be supportive and understanding (Lindström 1995, Wood & Pistrang 2004) and the relationship may remain important, even after discharge (Hautala‐Jylha et al . 2005).…”
Section: Discussionmentioning
confidence: 71%
“…However, recent SWLStG national patient survey (Care Quality Commission 2008) indicates that service users are happier with the treatment they are receiving. An appreciated relationship is considered to be a positive way to promote care commitment (Hautala-Jylha et al 2005); these findings would therefore suggest that continuity of care has improved.…”
Section: Discussionmentioning
confidence: 96%
“…Many studies demonstrate that continuity of care is premised on a good and stable relationship between patient and provider, and that a good patient-provider relation is vital for the mental health service users to feel they are being helped [10111213141819]. Two of three studies of patients’ experience of continuity referred to the importance of the therapeutic relationship [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic appraisal of the literature, supplemented by interviews with patients and families, Joyce et al [9] found that continuity of care has been defined in terms of service delivery, accessibility, relationship base and individualized care. In Parker et al’s [10] review of continuity of care-studies based on users’ experiences, they identify the following factors: users’ relationships with the providers, understanding of their condition and treatment, coordination of care, what happened to them during transition, their personal agency, and their existence as a “whole person.” Many studies show the importance of a good cooperative relationship between user and their provider [11121314]. …”
Section: Introductionmentioning
confidence: 99%